1995
DOI: 10.1136/jech.49.5.482
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviours explain part of the differences in self reported health associated with partner/marital status in The Netherlands.

Abstract: Study objective -To describe the differences in health behaviours in disparate marital status groups and to estimate the extent to which these can explain differences in health associated with marital status.Design -Baseline data of a prospective cohort study were used. Directly age standardised percentages of each marital group that engaged in each ofthe following behaviours -smoking, alcohol consumption, coffee consumption, breakfast, leisure exercise, and body mass indexwere computed. Multiple logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
2
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 33 publications
4
83
2
2
Order By: Relevance
“…A spouse, whether male or female, can provide personal care [35], which may have other kinds of beneficial effects such as support. In addition, a spouse can stimulate positive health behaviors [36]. It is suggested that a male spouse may not be as effective as a caregiver for women [37], which makes men more dependent on their woman and women more dependent on a caregiver, because their husband has already died.…”
Section: Discussionmentioning
confidence: 99%
“…A spouse, whether male or female, can provide personal care [35], which may have other kinds of beneficial effects such as support. In addition, a spouse can stimulate positive health behaviors [36]. It is suggested that a male spouse may not be as effective as a caregiver for women [37], which makes men more dependent on their woman and women more dependent on a caregiver, because their husband has already died.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, healthier individuals are more likely to maintain relationships and individuals who are in relationships experience the protective effects they may offer. Specific reasons suggested (and to varying degrees supported by empirical research) for the positive affects of romantic relationships on health include: social support (Robles and Kiecolt-Glaser 2003;Seeman and Syme 1987), economic support (Hahn 1993;Wilson 2001), greater social integration and protection from stress among couples (Hahn 1993;Lewis 1997), an increased sense of meaning and purpose in life that may accompany a romantic relationship (Antonovsky 1979), and romantic partners' encouragement of positive health beliefs and health behaviors (Joung et al 1995;Markey et al 2005). In other words, an individual's physical and psychological experiences are affected by their relationships.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the proportion of diabetes mellitus among women in general living together with someone was significantly lower than that of those living alone [29], and this result was similar to ours. Generally, support from a partner might explain the lower proportion of diabetes mellitus among married persons [30,31]. Although our findings from this study would suggest that support for schizophrenic women by medical staff or family members, but not by husbands, was important, the association between diabetes mellitus and living arrangement or marital status among patients with schizophrenia needs to be confirmed by other cohorts.…”
Section: Discussionmentioning
confidence: 51%